Dew point temperature as an invariant replacement for relative humidity for advanced perovskite solar cell fabrication systems. Issue 42 (15th August 2018) - Ko, Yohan; Lee, Chanyong; Kim, Youbin; Kim, Yechan; Yun, Yong Ju; Jun, Yongseok
Abstract : We highlight dew point temperature as a universal parameter affecting the formation of organic–inorganic halide perovskite films. Abstract : The ambient environment plays a pivotal role in the formation of organic–inorganic halide perovskite films. In particular, a certain level of humidity during the fabrication process can promote the crystallization of perovskites, resulting in better film morphologies and enhanced photovoltaic performances. Here, we unravel the importance of thermal equilibrium on the effect of relative humidity during perovskite film fabrication. We show that crystal quality is highly influenced by the dew point even when the relative humidity is unchanged. Observations related to the importance of the dew point on the material morphology, crystal quality, and resultant photovoltaic properties shed light on the dew point as a universal parameter affecting perovskite film fabrication.